Model Perilaku Pencarian Informasi Guna Memenuhi Kebutuhan Informasi: - Hasana, Tamara Nur; Daulay, Ardiani; Sasmita, Febry Dwi; Atika, Mutia; Purwaningtyas, Franindya (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
A pattern of human behavior in informational situations, including the use and seeking of information, is known as information behavior. The conduct being discussed here is the process through which a person acquires information. According to David Ellis, Eisenberg, and Berkowitz, the research methodology involves literature studies. The Big Six Skills Model is connected to the information search stages Eisenberg and Berkowitz have proposed. Task definition, information search technique, location and access, information utilization, synthesis, and evaluation are the first steps. The information search process can be modeled using the stages listed above. Both the need and our information needs will be met, which will give us a sense of contentment. Keywords: Information, Information Needs, Information Search, Model of Information Search